A Shift in Perspective: A Role for the Type I Toxin TisB as Persistence-Stabilizing Factor - Edelmann, Daniel; Berghoff, Bork A. (Frontiers in Microbiology, 2022)
Bacterial persistence is a phenomenon that is founded by the existence of a subpopulation of multidrug-tolerant cells. These so-called persister cells endure otherwise lethal stress situations and enable restoration of bacterial populations upon return to favorable conditions. Persisters are especially notorious for their ability to survive antibiotic treatments without conventional resistance genes and to cause infection relapse. The persister state is typically correlated with reduction or inhibition of cellular activity. Early on, chromosomal toxin-antitoxin (TA) systems were suspected to induce the persister state in response to environmental stress. However, this idea has been challenged during the last years. Especially the involvement of toxins from type II TA systems in persister formation is put into question. For toxins from type I TA systems the debate has just started. Here, we would like to summarize recent knowledge gained for the type I TA system tisB/istR-1 from Escherichia coli. TisB is a small, membrane-targeting toxin, which disrupts the proton motive force, leading to membrane depolarization. Based on experimental data, we hypothesize that TisB primarily stabilizes the persister state through depolarization and further, secondary effects. We will present a simple model that will provide a framework for future directions.